GPCR–styrene maleic acid lipid particles (GPCR–SMALPs): their nature and potential. (11th April 2016) - Wheatley, Mark; Charlton, Jack; Jamshad, Mohammed; Routledge, Sarah J.; Bailey, Sian; La-Borde, Penelope J.; Azam, Maria T.; Logan, Richard T.; Bill, Roslyn M.; Dafforn, Tim R.; Poyner, David R.
Abstract : G-protein-coupled receptors (GPCRs) form the largest class of membrane proteins and are an important target for therapeutic drugs. These receptors are highly dynamic proteins sampling a range of conformational states in order to fulfil their complex signalling roles. In order to fully understand GPCR signalling mechanisms it is necessary to extract the receptor protein out of the plasma membrane. Historically this has universally required detergents which inadvertently strip away the annulus of lipid in close association with the receptor and disrupt lateral pressure exerted by the bilayer. Detergent-solubilized GPCRs are very unstable which presents a serious hurdle to characterization by biophysical methods. A range of strategies have been developed to ameliorate the detrimental effect of removing the receptor from the membrane including amphipols and reconstitution into nanodics stabilized by membrane scaffolding proteins (MSPs) but they all require exposure to detergent. Poly(styrene-co-maleic acid) (SMA) incorporates into membranes and spontaneously forms nanoscale poly(styrene-co-maleic acid) lipid particles (SMALPs), effectively acting like a 'molecular pastry cutter' to 'solubilize' GPCRs in the complete absence of detergent at any stage and with preservation of the native annular lipid throughout the process. GPCR–SMALPs have similar pharmacological properties to membrane-bound receptor, exhibit enhanced stability compared with detergent-solubilized receptors and being non-proteinaceous in nature, are fully compatible with downstream biophysical analysis of the encapsulated GPCR.